Honoring the trust : - Massy, William F. (Anker Publishing Company, Inc., 2003)
How does higher education honor (or dishonor) the trust that society places in it? While colleges and universities may perform an adequate job of educating students, this book argues that institutions might still improve their competency while reining costs.In Honoring the Trust, the author examines how the environment of higher education and institutional policies has led to shortfalls in education competency. Rather than simply list the flaws in higher education, this book presents a practical program for improving the quality of higher education without increasing spending or sacrificing other priorities. Based on research performed at the National Center for Postsecondary Improvement, it provides a description of the problems that are currently facing institutions of higher education, and envisions solutions to these problems.